Open Trial of an Acceptance-Based Behavior Therapy Intervention to Engage Newly Diagnosed HIV Patients in Care: Rationale and Evidence of Feasibility and Acceptability. (September 2015) - Moitra, Ethan; Chan, Philip A.; Stein, Michael D.
Successful linkage and retention in care of newly diagnosed individuals in the United States remains a significant gap in the HIV care continuum. This study assessed the acceptability and feasibility of an acceptance-based behavior therapy (ABBT) intervention to engage patients newly diagnosed with HIV in medical care. Nine patients were recruited over 4 months for this brief ABBT intervention, which consisted of two brief sessions, each lasting less than 20 min. The intervention was developed to promote psychological acceptance of the HIV diagnosis, thereby increasing patients' willingness to make informed disclosure of their status. Eight patients completed a 1-month follow-up assessment, and all approved of the intervention and its components. Over the 1-month period, participants showed increased acceptance, reduced perceptions of HIV stigmatization, and increased disclosure of HIV status to social supports. This pilot study provided support for the continued investigation of ABBT as an adjunctive intervention for newly diagnosed HIV patients who are at high-risk of dropping out of HIV care.